Wear behaviors and wear mechanisms of wrought magnesium alloy AZ31 fabricated by extrusion-shear. (February 2017) - Hu, H-J; Sun, Z; OU, Z-W; Wang, X-Q
Abstract: Extrusion-Shear (ES) process for magnesium alloy is a newly developed plastic deformation technique which combines direct extrusion (DE) with ECAP (equal-channel angular pressing). Grains of ES-processed magnesium alloys can be refined effectively and mechanical properties can be improved, but the tribological properties have not been studied. In this study, the wear behaviors and wear mechanisms of AZ31 magnesium alloy samples produced by direct extrusion (DE) and extrusion-shear (ES) technologies, respectively, have been evaluated by fiction coefficient and wear frequencies obtained from the dry sliding tests conducted at different loads and frequencies by using a high speed dry sliding test machine. SEM and EDS analyses technologies also have been used to analyze the wear surfaces and wear debris in different fiction conditions. Based on the results, the ES-processed samples show a better wear resistance than those prepared by DE process as the ES-process samples show a lower friction coefficient comparing to those fabricated by DE process at the same conditions of loads and wear frequencies. With the increase of normal loads and reciprocating frequencies, the wear mechanism change from mild wear (adhesion, abrasion and oxidation) to severe wear (delamination, plastic deformation and melting). Therefore, the extrusion ways have significant influences on the wear behaviors of the samples and that the wear resistance of AZ31 magnesium alloy can be improved by extrusion-shear. Highlights: Extrusion-Shear is a new plastic deformation technique which combines direct extrusion with equal channel angular pressing. ES-processed samples show a better wear resistance than those prepared by DE process. The wear mechanism change from mild wear to severe wear with the increase of normal loads and reciprocating frequencies.